Characterization of the complete chloroplast genome of Apocynum venetum L. (Apocynaceae). Issue 3 (2nd July 2020) - Bautista, Mary Ann C.; Xiao, Zhongqi; Zheng, Yan; Miao, Shenyu; Deng, Yunfei; Chen, Tao
Abstract: Apocynum venetum L. (Apocynaceae) or Luobuma is a widely known traditional medicine use to treat hypertension, relieve anxiety, soothe the nerves and promote diuresis. In this study, the complete chloroplast genome of this medicinal plant was determined through Illumina sequencing method. The A. venetum cp genome is 150, 897 bp in length, containing a small single copy region (17, 256 bp), a large single copy region (81, 957 bp), and a pair of IR regions (25, 842 bp). It encodes for a total of 131 genes, including 86 protein-coding genes, 8 rRNA genes, and 37 tRNA genes. Phylogenetic analysis also reveals that A. venetum is relatively close to Aganosma cymosa.